2009
DOI: 10.1177/1043463109103898
|View full text |Cite
|
Sign up to set email alerts
|

Power, Trust, and Institutional Constraints

Abstract: This article focuses on how institutions matter in generating relationships of trust in an environment of unequal power. Trust is seen as the truster's expectation that the trustee will act trustworthily out of moral commitment and/or interest in continuing the relationship. Using cross-sectional data from a survey conducted in 2006 on Swedish employment relations the authors show that perceived power asymmetries between an employee and his or her superior have a negative impact on trust. However, perceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…It is the health and social care personnel who primarily possess the power of knowledge and who should aim the power at the clients as well as sharing the knowledge with them in order to provide a more equal situation between the client and the health care and social service system. Both Lammers and Stapel (2009) and Oskarsson, Svensson, and Ö berg (2009) mention power as a factor which implies ways of moral thinking. When power is being exercised in an asymmetric power relation, there is a need for fair rules (Oskarsson, Svensson, and Ö berg 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the health and social care personnel who primarily possess the power of knowledge and who should aim the power at the clients as well as sharing the knowledge with them in order to provide a more equal situation between the client and the health care and social service system. Both Lammers and Stapel (2009) and Oskarsson, Svensson, and Ö berg (2009) mention power as a factor which implies ways of moral thinking. When power is being exercised in an asymmetric power relation, there is a need for fair rules (Oskarsson, Svensson, and Ö berg 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both Lammers and Stapel (2009) and Oskarsson, Svensson, and Ö berg (2009) mention power as a factor which implies ways of moral thinking. When power is being exercised in an asymmetric power relation, there is a need for fair rules (Oskarsson, Svensson, and Ö berg 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevailing institutional environment should also influence levels of trust. Previous studies have shown that impartial, uncorrupted, and equality-enhancing institutions help to generate relationships of trust (Cook, Hardin, & Levi, 2005;Delhey & Newton, 2003;North, 1990;Oskarsson, Svensson, & Öberg, 2009;Ostrom, 1990;Ostrom, 2000;Rothstein & Uslaner, 2005). A growing body of research has focused on the importance of local neighborhood conditions.…”
mentioning
confidence: 99%
“…Rules involving fair procedures help generate trust even when parties are unequal in power. This trust in turn promotes a willingness to enter into and implement agreements (Oskarsson et al 2009). A challenge, however, is to sustain the trust needed to move forward with the more ambitious provisions of the agreement.…”
Section: Discussionmentioning
confidence: 99%